2020
DOI: 10.7759/cureus.7595
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Synovitis, Acne, Pustulosis, Hyperostosis, Osteitis (SAPHO) Syndrome: Diagnostic Challenges and Treatment Approach

Abstract: Synovitis, acne, pustulosis, hyperostosis, osteitis (SAPHO) syndrome is a rare disease; however, more and more case reports have been published that increase the awareness of this disorder, especially in children. Clinically it presents as a combination of chronic recurrent multifocal osteomyelitis symptoms and skin manifestations. SAPHO treatment remains a challenge. In most cases, non-steroidal anti-inflammatory drugs are initially used, although a combination with other drugs is preferred. In addition, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Bone manifestations are the cornerstone of the diagnosis. They are axial in adults and peripheral multifocal in children with classic CMRO (chronic multifocal recurrent osteomyelitis) [4,[8][9][10][11]. The dermatologic component may precede the first signs of rheumatism by years or, on the contrary, may occur extremely late [3,4,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bone manifestations are the cornerstone of the diagnosis. They are axial in adults and peripheral multifocal in children with classic CMRO (chronic multifocal recurrent osteomyelitis) [4,[8][9][10][11]. The dermatologic component may precede the first signs of rheumatism by years or, on the contrary, may occur extremely late [3,4,12].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of these two diseases remains poorly understood. Three theories have been suggested regarding SAPHO syndrome: the genetic theory suspected in view of the presence of familial forms, certain HLA histocompatibility genes (HLA-A26, HLA-B27, HLA-B39, HLA-B61) and other predisposition genes located on chromosomes 1 and 18 [1,2,9,12,[18][19][20]; the infectious or post-infectious theory incriminating Cutibacterium acnes found in 67% of bone biopsy samples [14,19]; the immunologic theory based on the evidence of a significant secretion of various pro-inflammatory cytokines and TNF-alpha [1,2,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients with SAPHO syndrome have been shown to be associated with the existence of HLA-B27, suggesting a genetic predisposition (18). Other genetic studies have found that single nucleotide polymorphisms or copy number variations of NOD2 , LPIN2 , and PSTPIP2 genes seem to be related to the development of SAPHO syndrome (19,20). NOD2 gene mutation may lead to abnormal immune response to bacterial peptidoglycan by activating pro-inflammatory transcription factor nuclear factor-κB (11).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to keep this rare inflammatory disorder on the differential. Although there are no validated diagnostic criteria for SAPHO syndrome and inflammatory markers are often unhelpful, the diagnosis typically requires osteoarticular and dermatological manifestation combined with protracted symptoms over months to years that often improve with anti-inflammatories but then recur 10 . Bony and skin lesions, however, may not be present at the same time, and a thorough history and physical examination are necessary to aid in the diagnosis.…”
Section: Discussionmentioning
confidence: 99%